2015
DOI: 10.1371/journal.pone.0116581
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phenotypic and Genotypic Characterization of Salmonella spp. in Pig Farms and Slaughterhouses in Two Provinces in Northern Thailand

Abstract: Salmonella spp. are an important group of bacterial zoonotic pathogens which can cause acute food-borne diseases in humans. Pork products are the main source of salmonellosis, but the origins and transmission routes of the disease have not been clearly determined. The purpose of this study was to characterize Salmonella spp. isolated in pig production lines both from pig farms and from slaughterhouses in Chiang Mai and Lamphun provinces in northern Thailand. The study focuses on the association among serotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
(38 reference statements)
7
28
0
Order By: Relevance
“…Salmonella Weltevreden and S. Rissen have been reported to be the most common serotypes found in animal farms and retail meats in South and Southeast Asia (Sinwat et al, ; Tadee, Boonkhot, Pornruangwong, & Patchanee, ), which aligns with our findings in this study. In different geographical areas, the leading Salmonella serotypes isolated from retail meat varies, for example, S. Thompson in Iran (Sodagari, Mashak, & Ghadimianazar, ), S. Montevideo in the United States (Bosilevac, Guerini, Kalchayanand, & Koohmaraie, ) and S. Typhimurium in Denmark (Bruun et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Salmonella Weltevreden and S. Rissen have been reported to be the most common serotypes found in animal farms and retail meats in South and Southeast Asia (Sinwat et al, ; Tadee, Boonkhot, Pornruangwong, & Patchanee, ), which aligns with our findings in this study. In different geographical areas, the leading Salmonella serotypes isolated from retail meat varies, for example, S. Thompson in Iran (Sodagari, Mashak, & Ghadimianazar, ), S. Montevideo in the United States (Bosilevac, Guerini, Kalchayanand, & Koohmaraie, ) and S. Typhimurium in Denmark (Bruun et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This study supports other research that multidrug resistance is less common amongst S. Rissen isolates when compared to the antibiotic resistance characteristics of S. Typhimurium isolates [19] [26]. However, S. Rissen displaying multidrug resistance has been recorded including a study conducted in Spain which identified 48 of 114 S. Rissen isolates as MDR ranging from four to nine antimicrobials [26] and Thailand where S. Rissen displayed resistance from one to five antibiotics [27].…”
Section: Discussionsupporting
confidence: 87%
“…In three publications, AMR was investigated in both E. coli and NTS isolates. The majority of publications included data from Thailand (20) [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] and Vietnam (15) [18,23,45,46,47,48,49,50,51,52,53,54,55]. One publication was found with data from each of Cambodia, Indonesia, Lao PDR and Malaysia [56,57,58,59].…”
Section: Resultsmentioning
confidence: 99%
“…The overall estimates for AMR in chickens, pigs, aquaculture, and other host species among studies for the 11 most common antimicrobials tested are shown in Figure 1 and Figure 2 for E. coli and NTS isolates, respectively. Data from two publications including AMR phenotypic results for NTS isolates from pigs and poultry combined [30,42] were not plotted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation